2006
DOI: 10.1136/qshc.2005.014845
|View full text |Cite
|
Sign up to set email alerts
|

Quality of diabetes care and coronary heart disease absolute risk in patients with type 2 diabetes mellitus in Australian general practice

Abstract: Objective: To examine the quality of diabetes care and prevention of cardiovascular disease (CVD) in Australian general practice patients with type 2 diabetes and to investigate its relationship with coronary heart disease absolute risk (CHDAR). Methods: A total of 3286 patient records were extracted from registers of patients with type 2 diabetes held by 16 divisions of general practice (250 practices) across Australia for the year 2002. CHDAR was estimated using the United Kingdom Prospective Diabetes Study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
46
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 12 publications
8
46
0
Order By: Relevance
“…This percentage was almost maintained during the follow-up period. Studies showed wide variation of the percentage of those who reached the LDL goal (15% to 87%) [30,31]. The problem in our study in addition to the modest control of LDL was that our PHC providers failed to make significant change in the number of controlled patients, dislike the findings of Ackermann study who reported the positive change of 20.5% [42].…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…This percentage was almost maintained during the follow-up period. Studies showed wide variation of the percentage of those who reached the LDL goal (15% to 87%) [30,31]. The problem in our study in addition to the modest control of LDL was that our PHC providers failed to make significant change in the number of controlled patients, dislike the findings of Ackermann study who reported the positive change of 20.5% [42].…”
Section: Discussionmentioning
confidence: 65%
“…These findings were far less than RECAP-DM study findings were 27% of diabetic patients in 7 European countries have HbA1c of <6.5%, (RECAP study) and 31% in CODE study and 33.5% in US study [28,29]. Other study showed even better HbA1c readings which reached up to 47% [30,31].…”
Section: Discussionmentioning
confidence: 88%
“…[3][4][5] However, as shown in many observational studies in primary care, only about half of those patients who have type 2 diabetes achieve this. [6][7][8][9] There are several reasons for this quality gap.…”
Section: Introductionmentioning
confidence: 99%
“…People with diabetes are two to four times more likely to develop cardiovascular disease and about two thirds die from it. Wan, et al (2006) ;Taggart, et al (2008) Undiagnosed kidney disease is also common in people with diabetes.…”
mentioning
confidence: 99%
“…Even among those with severe conditions, only half were provided with 15 Middleton, et al (2005) 16 Afkarian, et al (2013) 17 Wan, et al (2006) 18 Australian Bureau of Statistics (2008) specific psychological or pharmacological treatment. 19 There has been considerable expansion of primary health services in the meantime, but significant concerns about their distribution and entitlements to services remain.…”
mentioning
confidence: 99%